2019
DOI: 10.5505/kjms.2019.95530
|View full text |Cite
|
Sign up to set email alerts
|

The Physiologic and Radiologic Outcomes of Decortication for Chronic Empyema in the Long Term Follow Up: A Retrospective Analysis

Abstract: Aim: Chronic empyema due to non-specific or tuberculosis lead to both decrease in pulmonary functions and distortions of the radiologic views. Decortication either through video assisted thoracic surgery (VATS) or open thoracotomy is the last resort of treatment. The study aims to evaluate the spirometry and radiologic outcomes of decortication of patients with chronic empyema. Material and Method: The study included all patients who had decortication due to thoracic empyema between 2010 and 2016. Besides rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…When loculated pleural effusions occur, surgical interventions should be used aggressively to ensure lung expansion [9,10]. It has been demonstrated that lung expansion can be achieved successfully and with a less invasive surgery compared to thoracotomy, with rapid decision-making and early VATS application, primarily in stage 2 empyema when lung expansion cannot be achieved after tube thoracostomy [9][10][11][12][13]. In addition, studies are reporting that thoracoscopic debridement reduces morbidity by providing early recovery in the treatment of advanced empyema [14].…”
Section: Discussionmentioning
confidence: 99%
“…When loculated pleural effusions occur, surgical interventions should be used aggressively to ensure lung expansion [9,10]. It has been demonstrated that lung expansion can be achieved successfully and with a less invasive surgery compared to thoracotomy, with rapid decision-making and early VATS application, primarily in stage 2 empyema when lung expansion cannot be achieved after tube thoracostomy [9][10][11][12][13]. In addition, studies are reporting that thoracoscopic debridement reduces morbidity by providing early recovery in the treatment of advanced empyema [14].…”
Section: Discussionmentioning
confidence: 99%
“…It cannot be treated with anti-tuberculous drugs alone and needs surgical evacuation of the pus. Surgical techniques range from tube thoracostomy, intrapleural fibrinolytics, open window thoracostomy to thoracotomy and decortication [ 7 , 8 ]. These surgical techniques are recommended in conjunction with chemotherapy like anti-tuberculosis therapy (ATT) in cases of CTE.…”
Section: Introductionmentioning
confidence: 99%